Petroleum-based safe process oils in NR, SBR and their blends: Study on unfilled compounds. Part I oil characteristics and solubility aspects - Petchkaew Anida; Enschede; Noordermeer WMJacques; Sahakaro Kannika; TheNetherlands (Kautschuk Gummi Kunststoffe, 2013)
The petroleum-based safe process oils for replacement of DAE are: TDAE, MES and NAP. This work investigates the characteristics of DAE, TDAE and MES oils and solubility in NR, SBR and 50/50 NR/SBR. The solubility parameters are calculated based on the ground contribution method, and the values between oils and rubbers are correlated with the mass swelling of lightly crosslinked NR and SBR at different temperatures.A smaller triangle means better solubility of oil in the rubber which is confirmed by the higher level of oil uptake in the rubber. At high temperature in the range of mixing conditions, MES oil shows less compatibility compared to TDAE and DAE, respectively. Compatibility compared to TDAE and DAE, respectively.
Keywords: DAE; MES; NR; Polycyclic aromaticc; SBR; TDAE